Central Cascadia subduction zone creep. (30th April 2014) - Schmalzle, Gina M.; McCaffrey, Robert; Creager, Kenneth C.
Abstract Central Cascadia between 43°N and 46°N has reduced interseismic uplift observed in geodetic data and coseismic subsidence seen in multiple thrust earthquakes, suggesting elevated persistent fault creep in this section of the subduction zone. We estimate subduction thrust "decade‐scale" locking and crustal block rotations from three‐component continuous Global Positioning System (GPS) time series from 1997 to 2013, as well as 80 year tide gauge and leveling‐derived uplift rates. Geodetic observations indicate coastal central Oregon is rising at a slower rate than coastal Washington, southern Oregon and northern California. Modeled locking distributions suggest a wide locking transition zone that extends inland under central Oregon. Paleoseismic records of multiple great earthquakes along Cascadia indicate less subsidence in central Oregon. The Cascade thrust under central Oregon may be partially creeping for at least 6500 years (the length of the paleoseismic record) reducing interseismic uplift and resulting in reduced coseismic subsidence. Large accretions of Eocene age basalt (Siletzia terrane) between 43°N and 46°N may be less permeable compared to surrounding terranes, potentially increasing pore fluid pressures along the fault interface resulting in a wide zone of persistent fault creep. In a separate inversion, three‐component GPS time series from 1 July 2005 to 1 January 2011 are used to estimate upper plate deformation, locking between slow‐slip events (SSEs), slip from 16 SSEs and an earthquake mechanism. Cumulative SSEs and tectonic tremor are weakest between 43°N and 46°N where partial fault creep is increased and Siletzia terrane is thick, suggesting that surrounding rock properties may influence the mode of slip.